A new simplified sensorless direct stator field-oriented control of induction motor drives - Youssef, Omar E. M.; Hussien, Mohamed G.; Hassan, Abd El-Wahab (Frontiers in Energy Research, 2022)
Field-orientation scheme is a typical control technique of induction motors to obtain sophisticated performance. Stator field oriented control is less sensitive to parameter variations than rotor field oriented control. In addition, the estimation of the stator flux is more accurate than the rotor flux. Therefore, stator flux system is considered as a good choice for variable speed drives. However, the traditional configuration of the system includes four PI controllers which need effort in tuning. In this paper, simple calculations are proposed such that the configuration and performance of stator field oriented control system are improved by including only two PI controllers. In addition, with the aided of the machine phase axes, a simple procedure for the speed estimation target is suggested to effectively estimate the rotor speed of the machine with a direct estimation without any need for PI controller or additional observers in the speed observer procedure. The obtained results confirm the effectiveness of the proposed control scheme.